The supportive meaning and its relation with the ethical limits in ethnographic research with chronically ill children - Katerina Volcov (Universidade Federal de Santa Catarina, 2019)
Through the theoretical and practical references of ethnography, from a phenomenological perspective, this article presents reflections on the ethical limits of research with chronically ill children. From the presentation of an outpatient narrative of a child affected by atopic dermatitis, the concept of supportive meaning is developed as a requisite for parrhesia in order to establish a genuine exchange between researcher and informant. In this case, in addition to an ethical listening, the researcher must consider that the current state of the ill child requires a different perception and care from those related to the development of ethnographic research in other contexts.